Bond behavior between recycled coarse aggregate concrete and steel bar after salt-frost cycles - Su, Tian; Wu, Jin; Yang, Guixin; Zou, Zhenghao (Construction & building materials, 2019)
•The complete bond-slip curves of RAC with steel bar after salt-frost cycles were measured in this study.•The prediction model of the bond-slip between the RAC and steel bar after salt-frost cycles was established.•The influence of salt-frost cycles on bond stress distribution along with steel bars was investigated. This paper presents the experimental results of the salt-frost resistance of recycled coarse aggregate concrete (RAC) and the bond behavior of RAC with steel bar after salt-frost cycles. The results show that the mass of the RAC first increases and then decreases with increasing number of salt-frost cycles; the cubic compressive strength and the relative dynamic elastic modulus of the RAC decrease with increasing number of salt-frost cycles. The bond strength of the RAC decreases with increasing number of salt-frost cycles, while the slippage increases with increasing number of salt-frost cycles. The bond strength of the RAC after salt-frost cycles decreases more quickly and the slippage is larger than that after freeze-thaw cycles in water. The bond strength and the slippage of specimens without stirrups are lower than that with stirrups after salt-frost cycles. A prediction model of the bond-slip between the RAC and steel bar after salt-frost cycles is established, and the influence of salt-frost cycles on the bond stress distribution along with the steel bars is investigated.